(untitled) (World Bulletin of Management and Law, 2024)
Being one of the bodies in building the rule of law, the judiciary performs the function of monitoring the implementation of laws, supervision and prevention of violations of the law in the state. In this regard, the judicial system of the Republic of Uzbekistan faithfully performs its main function – the function of justice. But it should be noted that he went through quite laborious periods before reaching this level. In this article, the author reflects on the development of criminal courts in Uzbekistan